North Korea: Fading Totalitarianism in the Hermit Kingdom - Benjamin Katzeff Silberstein (Research Institute of Industrial Economics (IFN), 2010)
North Korea is perceived by many as one of the most totalitarian societies of modern time. But in the wake of the economic collapse of the 1990s, North Korean totalitarianism has grappled with new conditions. This paper examines how the countrys totalitarian character has been upheld through the institutional changes instigated by the economic collapse and subsequent famine in the country. It strives to answer whether todays North Korea should still be characterized as a totalitarian society, and, if not, what system then governs the country.
Keywords: P20; P30; P36; 330; North Korea; Totalitarianism; Authoritarianism; Institutional Change; Planned Economy; Social Control; Nordkorea; Diktatur; Planwirtschaft; Soziale Kontrolle; Institutioneller Wandel